KINETIKA PERTUMBUHAN SELULOSA MIKROBIAL TERHADAP PEMBUATAN NATA DE PINA DENGAN PENAMBAHAN SUKROSA - Tika Fadilah; Fajar Restuhadi (Fakultas Pertanian Universitas Riau, 2021)
Nata de pina is a food product derived from pineapple peel which part of the biomass growth consists of cellulose, agar-shaped, and white. The study aimed to determine the optimum production for sucrose concentration, yield, maximum velocity (Vmax), and Michaelis-Menten constant (KM) on the resulting microbial cellulose. The study used a non-factorial Completely Randomized Design (CRD) with four treatments and four replications. The treatments of this study were the addition of sucrose 1, 3, 6, and 9%. Data were analyzed statistically using analysis of variance. However, the effect of the treatments did not significantly (P>0.05) influence total sugar content. The results showed that growth kinetics of microbial cellulose with the addition of 6% sucrose was the optimum treatment to produce nata de pina, which had 0.81 cm thickness, 15.92 g wet weight, 12.92 g dry weight, 3.32% yield, and 7.04% total sugar content. The optimum growth of microbial cellulose biomass was obtain the maximum velocity value (Vmax) 1.4708 μM/mL minute and the optimum Michaelis-Menten constant (KM) with a value of 3.7341 μM.